Vers un paradigme des inter-relations sociales ? Pour une reconstruction du champ criminologique - Pires, Alvaro; Digneffe, Françoise (Criminologie, 1992)
One of the abiding debates in criminology contrasts social reactions to deviance with explorations of the causes in criminality. In this article, the authors note that the two paradigms consider crime in totally different ways, one as a raw fact, the other as a purely social construction. The authors propose a new paradigm which integrates at the same time contributions of sociology, clinical criminology from the School of Louvain, and feministic perspectives. This proposal differs from those advanced by left and right realists.